2022
DOI: 10.1115/1.4053089
|View full text |Cite
|
Sign up to set email alerts
|

Aeroelastic Analysis of a Single Element Composite Wing in Ground Effect Using Fluid–Structure Interaction

Abstract: The present work focuses on an advanced coupling of computational fluid dynamics (CFD) and structural analysis (FEA) on the aeroelastic behaviour of a single element inverted composite wing with the novelty of including the ground effect. The front wing of the Formula One (F1) car can become flexible under the fluid loading due to elastic characteristics of composite materials, resulting in changing the flow field and eventually altering overall aerodynamics. The purpose of this study is to setup an accurate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…However, in order to achieve coupling method stability, the focus should be on correlating the fluid and structural algorithms. The wing is considered as a tube type structure in the structural model, and our scope is to investigate the final shape of the wing affected by the fluid flow field [37]. Therefore, the effect of the structural damping is neglected as a modelling assumption.…”
Section: Numerical Modelling Of Two-way Coupling Fluid-structure Inte...mentioning
confidence: 99%
See 2 more Smart Citations
“…However, in order to achieve coupling method stability, the focus should be on correlating the fluid and structural algorithms. The wing is considered as a tube type structure in the structural model, and our scope is to investigate the final shape of the wing affected by the fluid flow field [37]. Therefore, the effect of the structural damping is neglected as a modelling assumption.…”
Section: Numerical Modelling Of Two-way Coupling Fluid-structure Inte...mentioning
confidence: 99%
“…The structural analysis consisted of a smaller number of grid cells in comparison with that of the fluid analysis. After the mesh sensitivity study was thoroughly conducted, it was concluded that the resultant wing performance is not significantly attributed to increase in the number of grid cells on the structural side [37]. The reason for not presenting a validation of the structural model is that there are no experimental data available for this particular problem in the literature.…”
Section: The Incompressible Fluid Model Due To the Low Mach Number Flowmentioning
confidence: 99%
See 1 more Smart Citation